Increased sensitivity of heavy metal bioreporters in transporter deficient Synechocystis PCC6803 mutants. - Gábor Patyi; Barbara Hódi; Dániel Solymosi; Imre Vass; Péter B Kós (PLoS ONE)
The detection and identification of heavy metal contaminants are becoming increasingly important as environmental pollution causes an ever-increasing health hazard in the last decades. Bacterial heavy metal reporters, which constitute an environmentally friendly and cheap approach, offer great help in this process. Although their application has great potential in the detection of heavy metal contamination, their sensitivity still needs to be improved. In this study, we describe a simple molecular biology approach to improve the sensitivity of bacterial heavy metal biosensors. The constructs are luxAB marker genes regulated by the promoters of heavy metal exporter genes. We constructed a mutant strain lacking the cluster of genes responsible for heavy metal transport and hence achieved increased intracellular heavy metal content of the Synechocystis PCC6803 cyanobacterium. Taking advantage of this increased intracellular heavy metal concentration the Ni2+; Co2+ and Zn2+ detection limits of the constructs were three to tenfold decreased compared to the sensitivity of the same constructs in the wild-type cyanobacterium.